Genomic Insights Into Sclerotinia Basal Stalk Rot Resistance Introgressed From Wild Helianthus praecox Into Cultivated Sunflower (Helianthus annuus L.) - Talukder, Zahirul I.; Underwood, William; Misar, Christopher G.; Seiler, Gerald J.; Cai, Xiwen; Li, Xuehui; Qi, Lili (Frontiers in Plant Science, 2022)
Crop wild relatives of the cultivated sunflower (Helianthus annuus L.) are a valuable resource for its sustainable production. Helianthus praecox ssp. runyonii is a wild sunflower known for its resistance against diseases caused by the fungus, Sclerotinia sclerotiorum (Lib.) de Bary, which infects over 400 broadleaf hosts including many important food crops. The objective of this research was to dissect the Sclerotinia basal stalk rot (BSR) resistance introgressed from H. praecox ssp. runyonii into cultivated sunflower. An advanced backcross quantitative trait loci (AB-QTL) mapping population was developed from the cross of a H. praecox accession with cultivated sunflower lines. The AB-QTL population was evaluated for BSR resistance in the field during the summers of 2017-2018 and in the greenhouse in the spring of 2018. Highly significant genetic variations (p < 0.001) were observed for the BSR disease in the field and greenhouse with a moderately high broad-sense heritability (H2) ranging from 0.66-0.73. Genotyping-by-sequencing approach was used to genotype the parents and the progeny lines of the AB-QTL population. A genetic linkage map spanning 1,802.95 cM was constructed using 1,755 SNP markers mapped on 17 sunflower chromosomes. A total of 19 BSR resistance QTL were detected on nine sunflower chromosomes, each explaining 2.21% to 16.99% of the phenotypic variance for resistance in the AB-QTL population. Sixteen of the 19 QTL had alleles conferring increased BSR resistance derived from the H. praecox parent. SNP markers flanking the identified QTL will facilitate marker-assisted breeding to combat the disease in sunflower.